2021
DOI: 10.1111/ijcp.14485
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of serum dynamic thiol/disulphide homeostasis and nitric oxide levels of total intravenous vs inhaled anaesthesia in endoscopic transsphenoidal pituitary surgery

Abstract: Background Transsphenoidal pituitary surgery (TPS) is traditionally performed under general anaesthesia. This study aimed to compare the effects of total intravenous anaesthesia (TIVA) or sevoflurane, an inhalation anaesthetic, on thiol‐disulphide homeostasis in patients undergoing endoscopic endonasal TPS. Methods In this study, 84 patients scheduled for TPS were randomly categorised into two groups: propofol (n = 42, the TIVA group) or sevoflurane (n = 42, the SEVO group). Blood samples were taken before ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
2
0
1
Order By: Relevance
“…Controlled hypotension established via medications such as nitroglycerin, nitroprusside, or esmolol, has also been extensively evaluated within the realm of ESS visualization, with no available evidence in TSA cohorts 61–63. Additional studies have investigated the effect of TIVA on temperature regulation, markers of oxidative stress, respiratory function, and neuroendocrine functional outcomes 64–67. Within this growing body of evidence multiple RCTs and systematic reviews focusing on ESS patients have demonstrated reductions in bleeding and improved surgical field visibility using TIVA relative to inhaled anesthetics 57–59.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Controlled hypotension established via medications such as nitroglycerin, nitroprusside, or esmolol, has also been extensively evaluated within the realm of ESS visualization, with no available evidence in TSA cohorts 61–63. Additional studies have investigated the effect of TIVA on temperature regulation, markers of oxidative stress, respiratory function, and neuroendocrine functional outcomes 64–67. Within this growing body of evidence multiple RCTs and systematic reviews focusing on ESS patients have demonstrated reductions in bleeding and improved surgical field visibility using TIVA relative to inhaled anesthetics 57–59.…”
Section: Discussionmentioning
confidence: 99%
“…[61][62][63] Additional studies have investigated the effect of TIVA on temperature regulation, markers of oxidative stress, respiratory function, and neuroendocrine functional outcomes. [64][65][66][67] Within this growing body of evidence multiple RCTs and systematic reviews focusing on ESS patients have demonstrated reductions in bleeding and improved surgical field visibility using TIVA relative to inhaled anesthetics. [57][58][59] Such improvements in surgical visualization must be weighed against the necessity of maintaining sufficient MAP for adequate coronary and cerebral blood flow during TSA.…”
Section: Intraoperative Interventions Total Intravenous Anesthesia (T...mentioning
confidence: 99%
“…La anestesia con bajo flujo y sevoflurano no crea ninguna diferencia en los parámetros hemodinámicos, por lo tanto, se puede usar con seguridad (23) . Por otro lado, en el postoperatorio de cirugía cardíaca y no cardíaca, diversos estudios han demostrado resultados promisorios del manejo anestésico preventivo del EOx (24)(25)(26) . Para esto hay que considerar los efectos específicos oxidantes y antioxidantes de los agentes anestésicos (2,27,28) .…”
Section: Efectos De La Anestesia Sobre El Estrés Oxidativo Y El Uso D...unclassified